Perception of Entrepreneurs Concerning Employment Skills in Information and Communication Technology (ICT) - Angelia Maharani Purba; Miduk Purba; Arlina Pratiwi (Jurnal Mantik, 2020)
The purpose of this research was to explore employers' perceptions of the five most important job skills they need graduates to have in order to graduates to be considered employable in the job market. The research data is obtained by a survey of entrepreneurs in the Riau Islands Province from various of companies that employ engineering information and communication technology. The research instrument was adopted from the technical accreditation board manual and the Malaysia Future of Engineering Education Report. Data from entrepreneurs were obtained from the information system of the Riau Islands Province Kadin in collaboration with the Riau Islands Province Kadin by circulating the instrument through the WA group and E-mail. Data were obtained from 119 entrepreneurs in the Riau Islands. Data were analyzed with descriptions of analysis using SPSS V 20. From the analysis carried out, it was seen from the average, the five most important job skills in a row: The ability of graduates to identify problems, apply problem-solving, solutions and formulations, the ability to present ideas effectively and self-confidence, the ability to design and conduct experiments, as well as analyze and interpret, the ability to function effectively as an individual and in a group, and the ability to continue to learn independently in acquiring new knowledge, technology and skills.